Between Development and Politics: The Decline of the Community Service Program in Indonesian Higher Education, 1960s – 1970s - Suwignyo, Agus; Sudarmadi, Tular; Wahyuni, Hermin Indah (Paramita: Historical Studies Journal, 2024)
Abstract: The 1961 official enactment of “community service” (CS) as one of the Indonesian higher education (HE) missions aimed to improve the welfare of the Indonesian society, among others, by eradicating illiteracy and poverty. However, the method for implementing CS depended heavily on the ideological orientation of the ruling political regimes. The present article examines why CS programs became marginalized in the management of Indonesian HE during the politically tumultuous years of the 1960s and 1970s. Employing a historical method and drawing upon data from university reports, newspaper articles, and government documents, this article argues that the implementation of CS programs took place asymmetrically with the nature of CS as a social mission. Political agendas of the different Indonesian governments systematically directed away the trajectories and targets of the CS program from its original mission of developing the welfare of the people. The CS programs, in practice, reflected the pragmatic political goals of the governments. Consequently, the Indonesian HE lost its transformative role in society. Abstrak: Disahkannya “pengabdian masyarakat” (PkM) pada tahun 1961 sebagai salah satu misi pendidikan tinggi (PT) Indonesia bertujuan untuk meningkatkan kesejahteraan masyarakat Indonesia, antara lain dengan memberantas buta huruf dan kemiskinan. Namun, metode penerapan PkM sangat bergantung pada orientasi ideologi rezim politik yang berkuasa. Artikel ini mengkaji mengapa program PkM menjadi terpinggirkan dalam pengelolaan perguruan tinggi Indonesia selama tahun-tahun politik yang penuh gejolak pada tahun 1960an dan 1970an. Dengan menggunakan metode historis dan memanfaatkan data dari laporan universitas, artikel surat kabar, dan dokumen pemerintah, artikel ini berargumentasi bahwa implementasi program PkM terjadi secara asimetris dengan sifat PkM sebagai misi sosial. Agenda politik dari berbagai pemerintahan di Indonesia secara sistematis mengalihkan arah dan sasaran program PkM dari misi awalnya untuk mengembangkan kesejahteraan masyarakat. Program PkM pada praktiknya mencerminkan tujuan politik pragmatis pemerintah. Akibatnya, PT Indonesia kehilangan peran transformatifnya dalam masyarakat.